Financial Literacy and Capital Access Training for Women Microentrepreneurs - Muhammad Abduh; Hukma Ratu Purnama; Muhammad Dzaky Firdaus; Muliadi Bandu (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This Community Service Activity (PKM) aims to improve women micro-entrepreneurs' understanding of financial literacy and business financial management, and to expand their access to formal capital. The program is designed to strengthen participants' capacity to manage business finances effectively and utilize various safe and legal sources of capital. Research Design and Methodology: The PKM program was implemented using a socialization, education, and practical training approach through presentations, discussions, question-and-answer sessions, and demonstrations of simple bookkeeping. Participants were also introduced to financial technology, such as digital wallets, and strategies for obtaining financing from formal financial institutions. The program targeted 15–25 women micro-entrepreneurs from the PKK group in Padanglampe Village. Findings and Discussion: This activity successfully increased participants' understanding of the importance of structured business financial management and the use of financial technology to support business operations. Participants gained insight into formal sources of capital and understood the risks of informal loans. They also showed enthusiasm for applying simple bookkeeping and learning strategies to secure capital from formal financial institutions. Implications: This program makes an essential contribution to promoting women's economic independence in rural areas and strengthening community financial literacy. It is hoped that this activity will become a sustainable model that can be replicated in other target areas while also supporting the long-term capacity-building of women's MSMEs.